Constraint specifications for domain-specific systems: ontology-driven approach. (18th May 2019) - Banerjee, Shreya; Sarkar, Anirban
Well-formed Domain Specific Modelling Languages (DSML) are devised based on well-defined sets of syntaxes and semantics. These precisions are obtained raising at abstraction levels in domain specifications. Yet, appropriate representations of constraints are also important to limit meanings of generic concepts to different abstraction levels in a DSML. To address this issue, in this paper, a constraint specification language is developed. This proposed language is capable to restrict meanings of general concepts represented in an upper level ontology - Generalised Ontology Modelling (GOM) (Banerjee and Sarkar, 2016b) to domain specific systems in a systematic way. Further, several automated methods impose distinct constraints at different levels of abstractions in domain specific modelling. These methods also validate distinct constructs and constraints in domain specific systems against general concepts of GOM. The applicability of the proposed work is proved using couple of case studies based on applications in data-intensive and service-based domains.